The description of students learning difficulties in reaction rate materials - Della Rezkyta Amanda; Fajriah Azra (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2023)
Reaction Rate is material that high school students study in class XI MIPA in odd semesters. In this material, as much as 77.64% of SMAN 16 Padang class XI MIPA students have yet to achieve the minimum criteria set. It indicates that students have learning difficulties. Learning difficulties are failures in achieving learning goals characterized by low learning outcomes. This study aims to determine the percentage of students who experience learning difficulties for each indicator on the material reaction rate and determine the factors that cause learning difficulties experienced by students in terms of learning methods. This research is a type of descriptive research. The sample for this research was students in class XI MIPA 3 at SMAN 16 Padang in the 2022/2023 academic year, which consisted of 36 people. The research instruments used were two-tier multiple-choice diagnostic tests, questionnaires, and interviews. The data analysis used is descriptive, namely analyzing and providing an understanding of the data in the form of numbers so that an overview can be given in an orderly, concise, and clear manner. The results of this study stated that students of SMAN 16 Padang experienced learning difficulties in tar material with a high category. The highest difficulty level is found in the 3rd indicator (Explaining the effect of surface area on the rate of reaction), which is equal to 83.33%. Learning difficulties experienced by students are caused by ineffective learning methods, such as making study schedules and carrying them out, reading and taking notes, repeating material, concentrating, and doing assignments.